AGU's Thriving Earth Exchange: Five Reasons to Join In. (5th November 2013) - Pandya, Raj; Galkiewicz, Julia; Williams, Billy; Furukawa, Harry
<x xml:space="preserve">Abstract</x> AGU has launched the Thriving Earth Exchange, a new initiative that supports communities as they protect themselves from hazards, adapt to a changing planet, and create sustainable futures. Through the program, AGU members will work with local leaders to contribute their Earth and space science expertise to these significant societal challenges.